Kantowski-Sachs Cosmology with Perfect Fluid Matter Distribution in the f(R,T) Gravity Theory - Muh. Fachrul Latief; A. Indra Wulan Sari Ramadani (Lambung Mangkurat University Press, 2026)
This research investigates the exact solution of the Kantowski-Sachs metric within the framework of gravity theory, with the matter distribution described as a perfect fluid. The gravitational field equations are first derived using the modified Einstein-Hilbert action principle. Next, the system of field equations is solved by applying the assumption that the expansion scalar is proportional to the shear scalar , thus obtaining a relationship between the Kantowski-Sachs metric coefficients. The obtained solution is used to analyze several physical parameters, including the Hubble parameter , spatial volume , expansion scalar , shear scalar , deceleration parameter , and jerk parameter . The results show that the model describes an anisotropic universe that begins from a Big Bang-type singularity, undergoes a decelerating expansion phase, and produces a jerk parameter value greater than the prediction of the model. These findings indicate a deviation in the expansion dynamics of the early universe, although the interpretation is still limited by the assumption of proportionality and the selection of a specific form of the function . Therefore, further testing of observational data is necessary to assess the validity of this model.